Case Study on the Rupture Morphology of a Copper Tube in an Air Conditioner Condenser After Fire - Yunlong Ou; Ming Fu; Jing Zhang; Wenzhong Mi; Changzheng Li; Shouhai Chen; Shoulei Zheng (Fire)
The new eco-friendly flammable refrigerant in air conditioners has resulted in an annual increase in fire incidents associated with these units. Fire investigators face significant challenges in identifying the causes of these fires. In this study, copper tube samples were extracted from various locations of air conditioner condenser debris post fire. The morphology characteristics of the ruptured copper tubes formed by a high-temperature flame in fire and that formed by corrosion were analyzed, respectively. The findings indicate that the ruptures in the copper tubes of air conditioners may be classified into two types based on their origins: ruptures resulting from fire and ruptures resulting from corrosion. The ruptures in the copper tubes resulting from fire are associated with the presence of aluminum alloy fins. At elevated temperatures, the copper and aluminum atoms persist in diffusing and fracturing. A significant quantity of silver-white aluminum is present surrounding the ruptures, and distinct elemental layers may be seen in the cross-section. The corrosion-induced ruptures in the copper tubes are associated with ant nest corrosion. Despite the influence of high-temperature flame melting on surface corrosion pits, they will not entirely obscure the pits and the cross-section continues to exhibit the bifurcated structure characteristic of ant nest corrosion. This investigation demonstrates that corrosion of ant nests is the root cause of copper tube breakage obscured by flames. An investigation method for the refrigerant leakage air conditioning fire is proposed. The above findings can provide proof and method for air conditioning fire investigation.